(untitled) (Research, Society and Development, 2023)
In the context of the fight against military dictatorship, the Brazilian Health Reform took place in the 1970s, a period marked by the population’s desire for more social rights, including the right to health. Thus, the Magna Carta presents health as a right of all and a duty of the state, establishing the bases for the creation of the Unified Health System (SUS). In situations where the State is unable to provide health services, including the supply of medicines, the phenomenon of judicialization of health emerges, where the judiciary acts to guarantee access to medicine. Thus, the objective of this research was to carry out a bibliographical research on the judicialization of access to medicines in Brazil. The study presents the bases of the fundamental right to health, combined with the understanding of higher courts that point to a congestion of processes with this object, amidst a scenario of State failure to provide medicines. Judicialization appears to be a tool capable of ensuring the right to health despite there currently being pending consideration of topic 1,234 in the STF. On the other hand, it is essential that the State understands the importance of public health in Brazil, reinforcing intersectoral cooperation to establish more appropriate criteria for the management of health resources and the adequate materialization of the right to health in the provision of medicines.